Whole-exome sequencing identified genetic risk factors for asparaginase-related complications in childhood ALL patients - Abaji, Rachid (Oncotarget, 2017)
Allergy, pancreatitis and thrombosis are common side-effects of childhood acute lymphoblastic leukemia (ALL) treatment that are associated with the use of asparaginase (ASNase), a key component in most ALL treatment protocols. Starting with predicted functional germline variants obtained through whole-exome sequencing (WES) data of the Quebec childhood ALL cohort we performed exome-wide association studies with ASNase-related toxicities. A subset of top-ranking variants was further confirmed by genotyping (N=302) followed by validation in an independent replication group (N=282); except for thrombosis which was not available for that dataset. SNPs in 12 genes were associated with ASNase complications in discovery cohort including 3 that were associated with allergy, 3 with pancreatitis and 6 with thrombosis. The risk was further increased through combined SNPs effect (p≤0.002), suggesting synergistic interactions between the SNPs identified in each of the studied toxicities. Interestingly, rs3809849 in the MYBBP1A gene was associated with allergy (p= 0.0006), pancreatitis (p=0.002), thrombosis (p=0.02), event-free survival (p=0.02) and overall survival (p=0.003). Furthermore, rs11556218 in IL16 and rs34708521 in SPEF2 were both associated with thrombosis (p=0.01 and p=0.03, respectively) and pancreatitis (p=0.02). The association of SNPs in MYBBP1A, SPEF2 and IL16 geneswith pancreatitis was replicated in the validation cohort (p ≤0.05) as well as in combined cohort (p=0.0003, p=0.008 and p=0.02, respectively). The synergistic effect of combining risk loci had the highest power to predict the development of pancreatitis in both cohorts and was further potentiated in the combined cohort (p=1×10(-8)). The present work demonstrates that using WES data is a successful “hypothesis-free” strategy for identifying significant genetic markers modulating the effect of the treatment in childhood ALL.